P3 Flap: Technique for Fingertip Reconstruction - Giovanna Petrella, MD; Norman Della Rosa, MD; Roberto Adani, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Fingertip amputations represent an important spectrum of injuries, and most are avulsions or crush trauma. There is no consensus about one single standard treatment, and a wide number of techniques are available. The authors present the P3 flap as an option for covering fingertip defects with bone exposure, avoiding painful scars in the pulp area, without a donor site. This study included 12 fingertips with amputated segment not available for replantation. Volar oblique fingertip defects and transverse amputations with bone exposure, not more proximal than Hirase Zone IIB, were included. Defects were less than 2 cm. The patients were followed up for an average of 6 months. The aesthetic and functional outcomes and fingertip discrimination recovery were evaluated at 6 months by the static two-point discrimination (2-PD) test and DASH score (quick version). The average postoperative 2-PD test at 6 months was 5.9 mm (range from 5 to 8 mm). The mean healing time of the fingertip was 4 weeks. Nail deformity was reported in three cases with level IIB of amputation. None of the P3 flaps failed, and local infection was not reported. The average DASH score at 6 months was 1.1. The mean time to return to work was 38 days (range from 30 to 53). The P3 flap proposed in this study demonstrates a reliable single-stage technique, performed under local anesthesia, for fingertip defect reconstruction, avoiding skin incision and scars in the pulp region and preserving digital length and nail bed.